Determinants of corporate social responsibility (CSR) and intrinsic job motivation: a case of Malaysian banking company - Chan, Tak Jie; Mohd Hasan, Nurul Ain (2016)
This study aimed to examine the relationship between dimensions of corporate social responsibility (CSR) practices and intrinsic job motivation of employees in one of the banking companies in Malaysia. The study utilised CSR framework by Bursa Malaysia with localised CSR best practices dimensions developed by Mohd Hasan (2013). Multistage sampling was employed in this study, whereby simple random sampling and cluster sampling were employed. A survey method was used in this study, whereby questionnaires were distributed to 110 bank staff (managerial and non-managerial), but with 37 valid responses received. A set of self-administered questionnaires was used as the instrument for the data collection. The data was then analysed using Spearman’s rho correlation test through the SPSS version 22.0. Based on the findings, all the dimensions namely; workplace, environment, community, and marketplace have a positive and moderate relationship with internal job motivation. Limitations of the study, implications of the findings, and suggestions for future study are also discussed.